DAMPAK BERITA HOAX TENTANG COVID-19 TERHADAP PELAKSANAAN PROTOKOL KESEHATAN OLEH MASYARAKAT: (Studi Kasus Group Whatsapp Keluarga) - Khanifah, Anisatul; Fauzi, Agus Mahfudz (Jurnal Ilmiah Dinamika Sosial, 2022)
Indonesia is one of the countries with a high index of spreading hoax news. During the Covid-19 pandemic, the spread of fake news has actually increased. issues around religion, politics and health are issues that are often discussed with sources that have a crisis of validity. This puts the public at risk of consuming hoax news which today can be accessed through conventional media and online media which will have an impact on the level of public trust in the government, especially in the implementation of health protocols. The focus of this research is to find out how the impact of hoax news has on the implementation of health protocols carried out by the community. The approach used is qualitative with case studies on whatsapp groups, the analysis technique in this study is Herbert Blumer's theory of symbolic interactionism, which includes the concepts of meaning, language and thought. This finding shows that the spread of hoaxes occurs because of the meaning formed by individuals who believe that the news is reliable. passing through the thinking process stage which then the thinking process relates to the formation process where the meaning used will become an instrument for the direction and formation of social action or behavior on the meaning created on the news earlier, one of which is the violation of health protocols due to the meaning created from hoax news about covid-19. Thus, the public needs to increase literacy regarding hoax news and how to respond to hoax news correctly so that the Indonesian people can become smart people and can overcome the co-19 pandemic.